Determinants for association and gRNA-directed endonuclease cleavage by purified RNA editing complexes from Trypanosoma brucei - Hernandez, Alfredo (2008)
U-insertion/deletion RNA editing in the single mitochondrion of ancient kinetoplastids is a unique mRNA maturation process needed for translation. Multi-subunit editing complexes recognize many pre-mRNA sites and modify them via cycles of three catalytic steps: guide-RNA (gRNA) mediated cleavage, insertion or deletion of uridylates at the 3’ terminus of the upstream cleaved piece, and ligation of the two mRNA pieces. While catalytic and many structural protein subunits of these complexes have been identified, the mechanisms and basic determinants of substrate recognition are still poorly understood. The current study defined relatively simple single- and double-stranded determinants for association and gRNA-directed cleavage. To this end, we used an electrophoretic mobility shift assay to directly score the association of purified editing complexes with RNA ligands, in parallel with U.V. photo-crosslinking and functional studies. The cleaved strand required a minimal 5’ overhang of 12-nt and a ~15-bp duplex with gRNA to direct the cleavage site. A second protruding element in either the cleaved or the guide strand was required unless longer duplexes were used. Importantly, the single-stranded RNA requirement for association can be upstream or downstream of the duplex, and the binding and cleavage activities of purified editing complexes could be uncoupled. The current observations together with our previous reports (Cifuentes-Rojas et al., 2005 and 2006) show that association, cleavage and full-round editing by purified editing complexes have distinct determinants that increase in complexity as these editing stages progress. Finally, we found that the endonuclease KREN1 in purified complexes photo-crosslinks with a targeted editing site. A model is proposed whereby one or more RNase III-type endonucleases in editing complexes mediate the initial binding and scrutiny of potential ligands, and subsequent catalytic selectivity triggers either insertion or deletion editing enzymes.